Technology-based mental healthcare models : a systematic review of the literature (2021)
Introduction: This systematic review summarises the existing evidence on the implementation of technology-based mental healthcare models in the primary care setting. Methods: A systematic search was conducted (MEDLINE, Embase, CENTRAL) in August 2019 and